Das Schwingungsspektrum von Ba₅(ReO₆)₂ - Baran, Enrique José (1976)
The infrared and laser-Raman spectra of crystalline Ba₅(ReO₆)₂ are reported and discussed. From the obtained spectroscopic data a calculation of force constants and mean amplitudes of vibration for the ReO₆⁵⁻ ion has been carried out.